2018
DOI: 10.1093/logcom/exx043
|View full text |Cite
|
Sign up to set email alerts
|

The universal homogeneous binary tree

Abstract: A partial order is called semilinear if the upper bounds of each element are linearly ordered and any two elements have a common upper bound. There exists, up to isomorphism, a unique countable existentially closed semilinear order, which we denote by (S2; ≤). We study the reducts of (S2; ≤), that is, the relational structures with domain S2, all of whose relations are first-order definable in (S2; ≤). Our main result is a classification of the model-complete cores of the reducts of S2. From this, we also obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…It is an ℵ 0 -categorical binary tree, but in contrast to T 2 , which is a meet-tree, no two incomparable elements have a meet. (See [1] for more details.) It might be interesting to ask whether it has a generic automorphism, but the methods based on Fact 2.9 used in this paper do not seem to apply directly.…”
Section: Treesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is an ℵ 0 -categorical binary tree, but in contrast to T 2 , which is a meet-tree, no two incomparable elements have a meet. (See [1] for more details.) It might be interesting to ask whether it has a generic automorphism, but the methods based on Fact 2.9 used in this paper do not seem to apply directly.…”
Section: Treesmentioning
confidence: 99%
“…We use a criterion for having a generic automorphism that was established by Truss [17,Theorem 2.1] and then improved to a characterisation independently by Ivanov [5,Theorem 1.2] and Kechris and Rosendal [9,Theorem 6.2]. Namely, to show that an ultrahomogeneous structure M with age K has a generic n-tuple of automorphisms, one needs to prove that the class K n of pairs (A, p) such that A ∈ K and p is an n-tuple of partial automorphisms of A, has the joint embedding property (JEP) and a version of the amalgamation property which we call the existential amalgamation property (EAP) 1 (see Fact 2.9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A structure over a finite relational language is homogenizable if we can add new relational symbols to the structure's signature representing a finite number of formulas, such that the new expanded structure is homogeneous (see Definition 2.2 for details). The homogenizable structures are found in a variety of areas of mathematics, especially when studying random structures or structures with some excluded subgraphs, also called H−free structures [2,3,4,7,14,16]. In 1953 Fraïssé [10] studied homogeneous structures and found that for each set of finite structures K satisfying the properties HP, JEP and AP there is a unique infinite countable homogeneous structure M such that K is exactly the set of finite substructures of M (up to isomorphism).…”
Section: Introductionmentioning
confidence: 99%
“…With further developments [4,7], canonical functions have become powerful tools in studying reducts. The robustness and relative ease of the methodology is becoming more evident as several classifications have been achieved by their use, e.g., [1,2,6,10,19,23].…”
mentioning
confidence: 99%